On Infinite Groups with Complemented Non-Abelian Subgroups - Baryshovets, P. P. (Ukrains’kyi Matematychnyi Zhurnal, 2013)
We present the description of locally finite groups containing at least one non-Abelian Sylow subgroup in which all non-Abelian subgroups are complemented.